Adaptive QoS control for real-time video communication over wireless channels. (18th November 2005) - Wu, Dapeng; Thomas Hou, Y.; Zhu, Wenwu; He, Zhihai; , Ya-Qin Zhang
Robust transmission of real-time video over wireless channels is a challenging problem. This is because the bit error rate (BER) in wireless channels is very high and the bit errors could have devastating effects on the video presentation quality. This paper addresses this problem by introducing adaptive quality-of-service (QoS) control for real-time video communication over wireless channels. The adaptive QoS control consists of optimal mode selection and delay-constrained hybrid automatic repeat request (ARQ). By combining the best features of error-resilient source encoding, forward error correction (FEC) and delay-constrained retransmission, our proposed adaptive QoS control system is capable of achieving bounded delay, high reliability, and efficiency.